A novel approach to expedite evidence to impact in pre-eclampsia: co-developed policy labs in Zambia and Sierra Leone - Katy Kuhrt; Chileshe Mabula-Bwalya; Harriet Boulding; Alice Beardmore-Gray; Alexandra Ridout; Osman Koroma; Betty Sam; Prince Tommy Williams; Francis Smart; Isabel Meleki; Meek Mwila; Mubanga Chileshe; et al. (BMC Global and Public Health)
Abstract Pre-eclampsia is a leading cause of maternal and neonatal mortality; 30,000 pre-eclampsia-related maternal deaths occur annually, with 70% in Sub-Saharan Africa (SSA) and 16% in South Asia. We have shown that early, accurate detection of hypertension combined with planned early delivery in women with late preterm pre-eclampsia significantly reduces stillbirth and severe maternal hypertension. We describe co-development and delivery of policy labs, working with The Policy Institute (King’s College London), and local stakeholders in Sierra Leone and Zambia, to expedite integration of new knowledge into pre-eclampsia care pathways, to improve care for women and babies with the worst outcomes. Policy labs are a unique, user-centric engagement approach, bringing diverse stakeholders together in co-designing strategies for translation of evidence into policy and impact. Both labs were facilitated by local, well-respected female team members, and addressed co-developed questions: ‘How can we improve timely detection and appropriate action in women with pre-eclampsia?’ (Sierra Leone); ‘What are enablers and barriers to offering planned early delivery between 34 and 37 weeks?’(Zambia). Participants at both labs identified lack of pre-eclampsia awareness as a key barrier, and recommended local co-design of community-based strategies to increase access to timely pre-eclampsia management. We demonstrated  policy labs as an effective approach in two low-and middle income settings to facilitate transfer of new knowledge into policy and action.